2012
DOI: 10.1002/eji.201242702
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA let‐7e is associated with the pathogenesis of experimental autoimmune encephalomyelitis

Abstract: MicroRNAs (miRNAs) play important roles in the regulation of immune responses. There is evidence that miRNAs also participate in the pathogenesis of multiple sclerosis (MS), but how the miRNAs regulate the pathogenesis of MS is still under investigation. The identification of new members of the miRNA family associated with the pathogenesis of MS could facilitate early diagnosis and treatment. Here we show that the level of miRNA let-7e is significantly upregulated in experimental autoimmune encephalomyelitis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
88
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 46 publications
6
88
1
1
Order By: Relevance
“…It has been demonstrated that Ahr plays a prominent role in EAE pathogenesis, and the activation of Ahr by TCDD ameliorates disease symptoms [5]. Recently, it has been revealed that several miRNAs are associated with the development of MS [28,29] and targeting specific miRNAs showed therapeutic potential in EAE [11][12][13]. However, the interaction between Ahr and miRNAs in EAE is yet unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that Ahr plays a prominent role in EAE pathogenesis, and the activation of Ahr by TCDD ameliorates disease symptoms [5]. Recently, it has been revealed that several miRNAs are associated with the development of MS [28,29] and targeting specific miRNAs showed therapeutic potential in EAE [11][12][13]. However, the interaction between Ahr and miRNAs in EAE is yet unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vivo studies have revealed the biological significance of certain miRNAs in autoimmune inflammation. MiR-155, miR-326, and let-7e are upregulated in EAE mice; deletion or silencing these miRNAs results in defects in the inflammatory T cells and attenuates disease symptoms [11][12][13]. Mice overexpressing miR-17-92 cluster in lymphocytes develop autoimmune conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, IL-10 is classified as a Th2 cytokine, and it has anti-inflammatory functions and suppresses Th1 cytokine production [22,23]. The expression level of let-7e was shown to be increased in infiltrated mononuclear cells in the brain and spinal cord of experimental autoimmune encephalomyelitis (EAE) mice [21]. It was also thought that let-7e modulates the balance of Th1/Th2 cytokines and the development of EAE by targeting IL-10 genes [21].…”
mentioning
confidence: 99%
“…The expression level of let-7e was shown to be increased in infiltrated mononuclear cells in the brain and spinal cord of experimental autoimmune encephalomyelitis (EAE) mice [21]. It was also thought that let-7e modulates the balance of Th1/Th2 cytokines and the development of EAE by targeting IL-10 genes [21]. Therefore, let-7e may be a principal regulator that controls the expression of IL-10 in various physiological and pathological processes, including autoimmune dis-accordance with the manufacturer's protocol.…”
mentioning
confidence: 99%
See 1 more Smart Citation